Robust Formation Control for Multiple Underwater Vehicles - Bechlioulis, Charalampos P.; Giagkas, Fotis; Karras, George C.; Kyriakopoulos, Kostas J. (Frontiers in Robotics and AI, 2019)
This paper addresses the distance-based formation control problem for multiple Autonomous Underwater Vehicles (AUVs) in a leader-follower architecture. The leading AUV is assigned a task to track a desired trajectory and the following AUVs try to set up a predefined formation structure by attaining specific distances among their neighboring AUVs, while avoiding collisions and enabling at the same time relative localization. More specifically, a decentralized control protocol of minimal complexity is proposed that achieves prescribed, arbitrarily fast and accurate formation establishment. The control signal of each vehicle is calculated based on the relative position of its neighbors and its own velocity only, which can be easily acquired by the onboard sensors without necessitating for explicit network communication. Finally, a realistic simulation study with 5 AUVs performing seabed scanning was conducted to clarify the approach and verify the theoretical findings of this work.